A Meta-analytic Review of the Relationship between Mathematics Anxiety and the Mathematical Thinking of Africa Students - , Oluwatoyin Motunrayo Atoyebi, Samuel Babajide Atoyebi (Archives of Current Research International, 2022)
The development of mathematical thinking is a crucial component of Mathematics education. Mathematics is needed for students to have the ability to manage, acquire, and make use of information to survive in competitive, uncertain, and ever-changing circumstances. Mathematical thinking is the primary goal of learning Mathematics. Despite the relative importance of Mathematics, it is highly disheartening to see that, due to Mathematics anxiety, students’ mathematical thinking has remained persistently subpar in Africa. Mathematics anxiety, which is the feeling of worry, stress, and trepidation when people engage with mathematics, has long been a topic of concern in education. This study investigated the relationship between Mathematics anxiety and the mathematical thinking of students in Africa. A meta-analysis method was used to statistically analyze the results of studies yielding 1789 samples that examined the relationship between Mathematics anxiety and the mathematical thinking of students. These studies were conducted from 2005 to 2021. The findings showed a strong negative correlation between Mathematics anxiety and the mathematical thinking of students in Africa. This study's statistical findings demonstrate how the problem-solving ability of students and the reasoning of students are affected by Mathematics anxiety. These results can help education stakeholders to create environments that will enhance students' mathematical reasoning abilities. This study recommends that curriculum developers should come up with strategies for incorporating fresh perspectives into the Mathematics curriculum that will make it engaging for African students and boost their thinking to become better not just in their academics but also in their day-to-day living.